IMPLIKASI SOSIAL DAN EKONOMI DARI AI DAN OTOMATISASI: TINJAUAN LITERATUR GLOBAL - Loso Judijanto; Untung Muhdiarta (JOURNAL OF COMMUNITY DEDICATION, 2024)
AI and automation can improve operational efficiency, but also pose challenges in the form of job shifts and the need for new skills. Social impacts include increased inequality if appropriate policies are not implemented. The literature highlights the need for an inclusive and collaborative policy approach between the government, private sector and public to mitigate the negative impacts and maximize the benefits of these technologies for society. Governments and other stakeholders are encouraged to invest in relevant education and training to ensure effective adaptation to these changes.